Tauromaquia —o ese extraño placer de la visualización de la muerte— - Cifuentes-Aldunate, Claudio (Diálogos Latinoamericanos, 2013)
The present article focuses on the practice of bullfighting and the significant thickness that goes beyond the simple act of the modern spectacle. It is an attempt to archaeological and semiotic reading of this practice, seen as a fossilized ritual of other older practices and meanings that drags on their way through the successive civilizations that have given its origin. The thickness of these readings does not rule out a possibility of psychoanalytic interpretation related with a reflection on the symbolic link between the bull and power. All those layers of significant thickness may explain the irrational fascination Spanish or Latin American people audience that assist and live, perhaps unthinkingly, (read unconsciously) forgotten symbols and rituals.